OASH DEEP FAULT ZONE: EARTH'S CRUST DYNAMICS - Ihnatyshyn, V.; Malytskyi, D.; Koval', Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A comprehensive study of seismotectonic processes in the Carpathian region is carried out to obtain data on modern geodynamics in the region. Observing present-day movements by strain metering reveals the prevalence of horizontal displacements in the Balkan Carpathians, particularly in the trans-Carpathian inner trough. One of the most efficient and accurate methods of indicating deformation is recording earth's surface deformation with quartz deformograph, which has sufficed considerable experimental material on the internal Carpathian Trough. Based on the monitoring data obtained from the field observation in Koroleve there were built diagrams of geophysical fields and seismicity in the region. The variations of slow deformations in the earth's crust are considered to be related to local seismic events. The paper presents a comparative analysis of the data on earth's crust movement that occurred in the region during 1999-2013 and those obtained from the previous studies. The data on the strain processes recorded in the region result from both tectonic processes in the earth's crust and meteorologic conditions (precipitations, water level in rivers, etc). Strain metering in the Oash deep fault zone during 2013 reveals rock expansion (the velocity value making +1104), which results from the earth's surface compression recorded for 1.5 years. Local seismic data show an anomalous acceleration of earth's crust movements, which is indicative of discernable seismic events in the region. The practical value of the work carried lies in determining the magnitude of strain in 2013, which makes +11.04 10-7, and is within the range of average annual values of the movements recorded in the Balkan Carpathians. Rock expansion is concluded to be a prevailing deformation. The value of strain during observation is 18097.635 nstr (180 10-7), and the average annual age progress makes +12.065 10-7.
Keywords: Carpathian region; seismotectonic processes; contemporary movements; geodynamic situation; strain-metering observations; Transcarpathian inner trough